Effect of trunk girdling on growth and crop yield of 'packham's triumph' pear - Machado B.D.* (2015)
The objective of this experiment was to evaluate the effect of girdling on vigor control and crop yield of the European pear cultivar 'Packham's Triumph' grafted on Pyrus calleryana rootstock. The experiment was planted in July 2010 in a commercial orchard on southern Brazil, using trees of 'Packham's Triumph' cultivar grafted on Pyrus calleryana rootstock. The treatments were different levels of cuts in the trunk: a) untreated; b) double girdle in 1/3 of the trunk; c) single girdle in 1/2 of the trunk; d) single girdling; e) double girdling. The first cut was made in September at 20 cm above the soil level, the second cut was made 10 cm above the first cut. The untreated trees had more vigor, with 7.93 m of annual growth. The double girdling reduced vigor by 34% compared with the untreated. Yield with the double girdling was 68.9 kg ha-1 which was 91% more than the untreated. The crop value with double girdling was increased by US$ 17.5 thousand compared with the untreated control. The use of trunk cutting and girdling in adult orchards decreased the vegetative growth of 'Packham's Triumph' pear trees. The double girdling increased crop yield in 'Packham's Triumph'.